MENINGKATKAN KEMAMPUAN BERHITUNG PERKALIAN SISWA MENGGUNAKAN METODE JARIMATIKA DI KELAS III SDI PLUS IMAM MUSLIM - Aisyah Zakiyah; Sony Tataq Setya; Sujoko Waluyo; Yetti Fauziah Silalahi (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
Mathematics is considered by elementary school students to be a difficult, boring and monotonous subject. Jarimatika learning media can be used to teach mathematics to students in a simple and easy to use way. Knowing how well Jarimatika media helps elementary school students in learning mathematics is the main aim of this research. Classroom action research (PTK) with a two-cycle approach was applied in this research. Twenty third grade students at SDI Plus Imam Muslim participated in this research. Strategy for gathering information in mathematics classes through the use of an action research model based on qualitative descriptive research. Based on these findings, it appears that the Jarimatical approach in learning mathematics can improve students' numeracy skills. Based on the results of the pre-cycle test which had an average score of 60, only 8 students successfully completed the learning objectives. With an average score of 75 in the first cycle exam, fifteen students in the first cycle were able to demonstrate mastery of the material. Twenty students in cycle II passed the second cycle exam with an average score of 82.75, indicating that they had acquired all the necessary knowledge. The findings of this research indicate that third grade students at SDI Plus Imam Muslim benefit from the Jarimatika approach in improving their multiplication calculation skills.